Forecasting Macroeconomic Indicators Of The Development Of The Ukrainian Economy During The War (2022–2023). - Verbivska, Liudmyla (Іnternational Journal for Quality Research, 2024)
The full-scale military invasion of the Russian Federation on the territory of sovereign Ukraine has led to the emergence of a number of destabilizing factors in the development of the Ukrainian economy. Moreover, it has caused the increase of macroeconomic instability and problems of a social - economic nature, which requires an immediate solution and development of forecasts of economic and social development. The purpose of the research is to forecast macroeconomic indicators of the economy development of Ukraine during the war (2022--2023). The forecasting results give evidence of the critical and threatening values of the analysed macroeconomic indicators of the Ukrainian economy development in war conditions. This causes a decrease in the life quality of the population and the sustainable competitiveness of the country and requires the formation and implementation of an effective macroeconomic policy. The substantiated influence of macroeconomic indicators on the level of life quality of the population indicates a strong interrelationship between the analysed indicators (R=0,933). The budget deficit in 2024 is forecast at the level of -2,7%; the GDP volume will decrease to 5,8%; the poverty level will increase to 62%, and the unemployment rate will increase to 33%.
Forecasting Macroeconomic Indicators Of The Development Of The Ukrainian Economy During The War (2022–2023).
Keywords: Macroeconomic Instability, Gross Domestic Product, Budget Deficit, Macroeconomic Indicators, Sustainable Economic.